Те, кто до нас: [повесть] / Лиханов А. - Лиханов Альберт Анатольевич (Круг чтения, 2019)
Плоскопечатный укрупненный шрифт Экземпляры: БС (20220518) / Инвентарный номер: 1119473 / Сис.шифр: 84(2) / Авт.знак: Л 65 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-4